2014
DOI: 10.9790/0853-135497101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aspiration VS non- aspiration techniques in fineneedle cytology of thyroid lesions

Abstract: AIM:To compare the efficacy of fine -needle non -aspiration cytology (FNNAC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Third, we did not assess other complications such as nerve damage, tissue trauma, tumor seeding, or vascular injury associated with both techniques, owing to a lack of data in the included studies. Finally, some studies reported that FNNAC combined with FNAC can obtain better quality cellular material [ 8 , 9 ], while other studies reported that a better diagnostic accuracy can be achieved by combining both techniques [ 13 , 23 , 26 ]. This suggests that a combination of both techniques may be more suitable for the investigation of patients with thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not assess other complications such as nerve damage, tissue trauma, tumor seeding, or vascular injury associated with both techniques, owing to a lack of data in the included studies. Finally, some studies reported that FNNAC combined with FNAC can obtain better quality cellular material [ 8 , 9 ], while other studies reported that a better diagnostic accuracy can be achieved by combining both techniques [ 13 , 23 , 26 ]. This suggests that a combination of both techniques may be more suitable for the investigation of patients with thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some studies reported that FNNAC combined with FNAC can obtain better quality cellular material, 15,16 while other studies reported that a better diagnostic accuracy can be achieved by combining both techniques. 17,18,19 In a similar study conducted by Srikanth et al, 1 Lymphadenopathy with highly cellular lesions like reactive hyperplasia and metastatic malignancy, both the techniques yielded comparable cellular material. In non-specific lymphadenitis, the non-aspiration technique was significantly better than aspiration technique with regard to background blood, amount of cellular material and retention of appropriate architecture.…”
Section: Resultsmentioning
confidence: 75%
“…Fine-needle aspiration cytology (FNAC) for tumours was first described by Martin and Ellis in the year 1930 in the United States [6].…”
Section: Introductionmentioning
confidence: 99%
“…Unsatisfactory specimens, especially mixed with blood, poses an obstacle to proper cytological interpretation. To overcome this problem, an alternative method of fine needle non-aspiration cytology (FNNAC) technique was developed which relies on the capillary pressure only to suck the cells inside the needle bore [6]. FNNAC is also known as cytopuncture was developed in France in 1982 by Brifford et al, originally was developed for vascular organs to avoid haemorrhage and to obtain less haemorrhagic cytology samples from breast lesions [6].…”
Section: Introductionmentioning
confidence: 99%